The Less You Are, the More You Are Helped: Effect of Kinesio Tape on Temporal Coordination - Bravi, Riccardo; Cohen, Erez James; Martinelli, Alessio; Gottard, Anna; Minciacchi, Diego (International Journal of Sports Medicine, 2018)
We investigated whether a relationship exists between the inherent timing skill of subject and the magnitude of effect of KT on timing performance by expanding the examination of the dataset described in our previous work. Healthy subjects, tested with and without KT (NKT), performed sets of repetitive wrist's flexion-extensions (IWFEs) with the dominant limb (DL) and the non-dominant limb (NDL) in a synchronization-continuation task at two inter-onset intervals (IOIs): 550-ms and 800-ms. Standard deviation (SD) of IWFEs was used to measure the unevenness of performance. Different patterns of response to KT were observed based on the participant’s inherent precision. In the NDL the effect of KT was found significantly higher in the subgroups of individuals having SDNKT of IWFEs>38 ms (p=0.0024) in the 800-ms IOI or SDNKT of IWFEs>19 ms (p=0.0004) in the 550-ms IOI. In the DL the effect of KT was not influenced by the inherent timing skill. We propose KT to be tested for restoring motor control on subjects experiencing sensorimotor disorders associated with intense repetitive training. Also, our findings suggest that care should be taken when using groups of healthy subjects to test the effect of KT.
Keywords: elastic bandage; rhythmic motor skills; motor control; upper limbs asymmetries